1989
DOI: 10.1002/ana.410260510
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography in manganese intoxication

Abstract: We employed 6-fluorodopa to study the integrity of the nigrostriatal dopaminergic projection by positron emission tomography in 4 subjects with clinical features of mild parkinsonism caused by exposure to manganese. The 6-fluorodopa scans were normal. This finding suggests that in early manganism sufficient to cause parkinsonian deficits, damage may occur in pathways postsynaptic to the nigrostriatal system, probably involving striatal or pallidal neurons. Fluorodeoxyglucose scans showed decreased cortical glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
47
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(59 citation statements)
references
References 15 publications
(5 reference statements)
9
47
2
Order By: Relevance
“…This finding is in accord with the 40-60% loss of dopaminergic cells seen in the nigrostriatal pathway of patients with IPD. In non-human primates and humans intoxicated with Mn, [ 18 F]-dopa (fluorodopa) PET scans are normal (Erikson et al, 1992;Kim et al, 1998;Shinotoh et al, 1995Shinotoh et al, , 1997Wolters et al, 1989). This supports the view that, in instances of Mn intoxication, the nigrostriatal pathway is relatively well preserved, consistent with many pathological observations showing that Mn-134 induced damage occurs primarily in pathways postsynaptic to the nigrostriatal system.…”
Section: Pet/spect As An Index Of the Integrity Of The Dopaminergic Nsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding is in accord with the 40-60% loss of dopaminergic cells seen in the nigrostriatal pathway of patients with IPD. In non-human primates and humans intoxicated with Mn, [ 18 F]-dopa (fluorodopa) PET scans are normal (Erikson et al, 1992;Kim et al, 1998;Shinotoh et al, 1995Shinotoh et al, , 1997Wolters et al, 1989). This supports the view that, in instances of Mn intoxication, the nigrostriatal pathway is relatively well preserved, consistent with many pathological observations showing that Mn-134 induced damage occurs primarily in pathways postsynaptic to the nigrostriatal system.…”
Section: Pet/spect As An Index Of the Integrity Of The Dopaminergic Nsupporting
confidence: 80%
“…DAT SPECT is more easily accessible and less expensive than is fluorodopa PET. Fluorodopa and DAT uptake values are (nearly) normal in patients with manganism (Huang et al, 2003;Kim et al, 1998;Shinotoh et al, 1997;Wolters et al, 1989), whereas uptake is markedly reduced in IPD patients. However, Guilarte et al (2008) reported that, in the non-human primate brain, chronic Mn exposure inhibited dopaminergic transmission, leading to motor deficits, in the absence of changes to presynaptic dopaminergic nerve terminals.…”
Section: Pet/spect As An Index Of the Integrity Of The Dopaminergic Nmentioning
confidence: 94%
“…It is predicted that fertilizer runoff is one of the predominant manmade sources of Mn enrichment in the riverine environment [18]. Zinc is present in high concentrations of 20 mg/kg -100.4 mg/kg in PRM and 20.3 mg/kg -95.4 mg/kg in POM.…”
Section: Fig 1 Figmentioning
confidence: 99%
“…4) The relationship between Mn neurotoxicity and PD is still debated, but at least Mn exposure is a risk factor for PD. 6,7) The mechanisms of Mn neurotoxicty remain unclear. Earlier reports suggested that Mn could enhance autooxidation of catecholamines and generate reactive oxygen species 8) and inhibit mitochondrial aconitase activity and disrupt mitochondrial energy production in the brain.…”
Section: Introductionmentioning
confidence: 99%